2012
DOI: 10.4103/2156-7514.94225
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Performance of Imaging Health Systems in Five Selected Hospitals in Uganda

Abstract: Objectives:The first objective of the study was to develop an index termed as the ‘Imaging Coverage’ (IC), for measuring the performance of the imaging health systems. This index together with the Hospital-Based Utilization (HBU) would then be calculated for five Ugandan hospitals. Second, was to relate the financial resources and existing health policy to the performance of the imaging systems.Materials and Methods:This was a cross-sectional survey employing the triangulation methodology, conducted in Mulago … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Training focussed on scaling up the numbers of human resource for imaging in these rural areas is key in increasing coverage and health-systems efficiency. [ 8 44 ]…”
Section: The Way Forward: Responsibility Of the State And Training Inmentioning
confidence: 99%
“…Training focussed on scaling up the numbers of human resource for imaging in these rural areas is key in increasing coverage and health-systems efficiency. [ 8 44 ]…”
Section: The Way Forward: Responsibility Of the State And Training Inmentioning
confidence: 99%
“…This calls for evidence-based planning, and purchasing of equipment. The disease burden within communities and at health facilities dictate on the type, level of technological sophistication and number of equipment to be purchased [ 14 , 15 ]. Use of evidence-based clinical imaging guidelines is also likely to improve appropriateness of imaging decisions and supposedly influencing management and treatment decisions, and hopefully impacting treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…One survey quantified the imaging needs in five selected hospitals in Uganda, based on the disease burdens in these hospitals and reported on how the existing imaging equipment addressed these needs, concluding that existing imaging equipment met only 36% of the imaging needs in these hospitals. This survey also reported that up to 50% of patients attending these selected hospitals required some type of imaging, but mostly ultrasound and X-ray [ 14 , 15 ]. For Uganda, the Atomic Energy Council (AEC) maintains an up to date countrywide inventory of radiology imaging devices.…”
Section: Introductionmentioning
confidence: 99%
“…The Radiology department provides ultrasonography and other imaging services. The ultrasound scan imaging modality is the second most common imaging modality in this department after general radiology 12 .…”
Section: Methodsmentioning
confidence: 99%